From water scarcity to sustainable water use in the West Bank, Palestine : dissertation submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of Doctor to be defended in public on Thursday, November 26, 2009 at 15:00 hours in Delft, the Netherlands /: dissertation submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of Doctor to be defended in public on Thursday, November 26, 2009 at 15:00 hours in Delft, the Netherlands. (2010) - Al-Nazer, Dima Wadi' H
No abstract available